Preparation method and application of antimony trioxide with low-temperature adaptability
Low-temperature adaptable antimony trioxide was prepared through nano-oxide auxiliary materials and multi-stage temperature-controlled oxidation reactions, which solved the problem of traditional antimony trioxide being easy to agglomerate at low temperatures and achieved excellent dispersibility and wide application in extremely cold environments.
Patent Information
- Application Number
- CN202510718197.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-10-03
AI Technical Summary
Traditional antimony trioxide easily agglomerates in low-temperature environments and has poor dispersion, which limits its application in extremely cold regions.
Nano zinc oxide, nano cerium oxide and nano titanium oxide are used as auxiliary materials, and antimony trioxide vapor is generated through a multi-stage temperature-controlled oxidation reaction and cooled at low temperature to form low-temperature adaptable antimony trioxide.
It significantly improves the dispersibility of antimony trioxide in low-temperature environments, broadens its application range in extremely cold regions, and meets the needs of flame retardant materials, coatings, ceramic sintering and electronic packaging.
Smart Images

Figure BDA0005428804000000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antimony trioxide preparation, and in particular to a preparation method of low-temperature adaptable antimony trioxide and application thereof. Background Art
[0002] Antimony trioxide, an important inorganic compound, is widely used in flame retardant materials, coatings, ceramics, and electronic packaging, and has attracted much attention due to its excellent flame retardant properties and chemical stability. Traditionally, antimony trioxide is prepared by heating and melting refined antimony metal, blowing air into it for oxidation to generate antimony trioxide vapor, which is then rapidly cooled to collect fine powder. However, the antimony trioxide obtained by traditional methods tends to agglomerate at low temperatures and has poor dispersibility, limiting its application in extremely cold regions. Summary of the Invention
[0003] In order to solve the above technical problems, the present invention provides a preparation method of low-temperature adaptable antimony trioxide and its application. The specific technical solution is as follows:
[0004] A method for preparing low-temperature adaptable antimony trioxide comprises the following steps:
[0005] a. Heat and melt the metal ladder to form antimony liquid;
[0006] b. adding a nanomaterial to the antimony solution, wherein the nanomaterial comprises at least one of nano-zinc oxide, nano-cerium oxide and nano-titanium oxide;
[0007] c. Blowing in an oxygen-containing atmosphere to carry out an oxidation reaction to generate antimony trioxide vapor;
[0008] d. Cooling the antimony trioxide vapor to 15-80°C to generate antimony trioxide powder;
[0009] e. Collecting the powder and post-processing it to obtain the low-temperature adaptable antimony trioxide.
[0010] Preferably:
[0011] In step a, the heating temperature is 530-650° C.;
[0012] In step b, the total mass of the nano-auxiliary materials is 0.03% to 0.05% of the mass of the antimony liquid, wherein the mass ratio of nano-zinc oxide, nano-cerium oxide and nano-titanium oxide is 1:1:0.5;
[0013] In step c, the oxidation reaction is carried out under multi-stage temperature control conditions, and the reaction temperature is 530-650°C.
[0014] Preferably, the multi-stage temperature control conditions specifically include:
[0015] Preheating stage: inject nano zinc oxide and nano cerium oxide mixed solution at 540-550℃;
[0016] Low temperature oxidation stage: at 570-600℃, with a temperature of 0.3-0.6m 3 / min flow rate to blow in oxygen;
[0017] High temperature strengthening stage: at 600-620℃, inject nano-titanium oxide and control the oxygen flow rate to 0.6-0.9m 3 / min;
[0018] Post-processing stage: at 550-570℃, control the oxygen flow rate to 0.3m 3 / min, and with a flow rate of 0.2m 3 / min nitrogen was blown in.
[0019] Preferably, the nano auxiliary material is a modified composite auxiliary material, which is obtained by compounding at least two of Al-ZnO, KH-570-CeO and N-TiO.
[0020] Preferably:
[0021] The Al-ZnO is prepared by the following steps: dispersing nano zinc oxide in deionized water, adding 0.5% aluminum nitrate by weight of the nano zinc oxide, adding 0.1M sodium hydroxide dropwise to a pH of 9.0, stirring at 60°C for 2 hours, washing, centrifuging, vacuum drying at 80°C for 12 hours, and calcining in air at 400°C for 3 hours;
[0022] The KH-570-CeO is prepared by the following steps: dispersing nano-cerium oxide in ethanol or deionized water, adding 0.5% by weight of KH-570, stirring at 70°C under nitrogen protection for 3 hours, washing, centrifuging, vacuum drying at 60°C for 10 hours, and heat treating at 150°C under nitrogen atmosphere for 2 hours;
[0023] The N-TiO is prepared by the following steps: dispersing nano-titanium oxide in ethylene glycol, adding 0.3% urea by weight, solvent thermal reaction at 180°C for 6 hours, washing, centrifuging, vacuum drying at 70°C for 12 hours, and calcining at 350°C under a nitrogen atmosphere for 2 hours.
[0024] Preferably, the multi-stage temperature control conditions specifically include:
[0025] Initial catalytic stage: Al-ZnO injection at 530°C, pretreatment for 20 min;
[0026] Preheating stage: inject KH-570-CeO at 550℃ and react for 25min;
[0027] Low temperature oxidation stage: at 560-580℃, with a flow rate of 0.25-0.45m 3 / min oxygen was introduced and the reaction was continued for 35min;
[0028] High temperature strengthening stage: at 590-610℃, control the oxygen flow rate to 0.55-0.75m 3 / min, reaction time 20min;
[0029] Post-processing stage: at 550-600℃, with a flow rate of 0.18m 3 / min nitrogen is blown in at a flow rate of 0.12m 3 / min, argon gas was blown in at a flow rate of 0.1m 3 A mixture of helium and oxygen was bubbled in at 1 / min for 33 min.
[0030] Preferably, in the post-processing stage:
[0031] When nitrogen is injected, the temperature is controlled at 580-600℃ and the oxygen flow rate is controlled at 0.25m 3 / min, lasting 15min;
[0032] When argon is injected, the temperature is controlled at 570-590°C and the oxygen flow rate is controlled at 0.1m 3 / min, lasting 10min;
[0033] When injecting helium, the temperature is controlled at 550-570℃ and the oxygen flow rate is controlled at 0.05m 3 / min, last for 8 minutes.
[0034] Preferably, the post-treatment includes low-temperature plasma treatment and ultrasonic redispersion.
[0035] The present invention also provides an application of low-temperature-adaptable antimony trioxide. The low-temperature-adaptable antimony trioxide prepared by any of the preparation methods described above is used for flame retardant materials, coatings, ceramic sintering and electronic packaging.
[0036] Preferably, the low-temperature adaptable antimony trioxide is used in flame retardant materials, coatings, ceramic sintering and electronic packaging, specifically including:
[0037] The antimony trioxide is used as a flame retardant for polyvinyl chloride, polypropylene or acrylonitrile-butadiene-styrene copolymer at 0 to -30°C.
[0038] The antimony trioxide is used for aviation or marine equipment coatings at 0 to -30°C.
[0039] The antimony trioxide is used for low temperature sintering of ceramics;
[0040] The antimony trioxide is added to electronic packaging as an antioxidant and moisture-proof additive.
[0041] The present invention provides a method for preparing low-temperature-adaptable antimony trioxide. By introducing nanomaterials (nano-zinc oxide, cerium oxide, and titanium oxide), the high specific surface area and catalytic activity of these materials are utilized to reduce the activation energy of the oxidation reaction, lowering the reaction temperature of conventional processes, reducing energy consumption, and minimizing thermal wear on equipment. Furthermore, the nanomaterials form a functional coating on the surface of the antimony trioxide particles, significantly improving their dispersibility in low-temperature environments and addressing the low-temperature agglomeration problem of antimony trioxide produced by conventional processes. DETAILED DESCRIPTION
[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0043] This embodiment provides a method for preparing low-temperature adaptable antimony trioxide, comprising the following steps:
[0044] a. Heat and melt the metal ladder to form antimony liquid.
[0045] b. adding nano-auxiliary materials to the antimony solution, wherein the nano-auxiliary materials include at least one of nano-zinc oxide, nano-cerium oxide and nano-titanium oxide.
[0046] c. Blow in an oxygen-containing atmosphere to carry out an oxidation reaction to generate antimony trioxide vapor.
[0047] d. Cool the antimony trioxide vapor to 15-80°C to generate antimony trioxide powder.
[0048] e. Collect the powder and post-process it to obtain low-temperature adaptable antimony trioxide.
[0049] The method for preparing low-temperature-adaptable antimony trioxide provided in this embodiment introduces nanomaterials (nano-zinc oxide, cerium oxide, and titanium oxide) and utilizes their high specific surface area and catalytic activity to reduce the activation energy of the oxidation reaction, lowering the reaction temperature of conventional processes, reducing energy consumption, and minimizing thermal wear on equipment. Furthermore, the nanomaterials form a functional coating on the surface of the antimony trioxide particles, significantly improving their dispersibility in low-temperature environments and addressing the low-temperature agglomeration problem of antimony trioxide produced by conventional processes.
[0050] Further:
[0051] In step a, the heating temperature is 530-650°C.
[0052] In step b, the total mass of the nano-auxiliary materials is 0.03% to 0.05% of the mass of the antimony liquid, wherein the mass ratio of nano-zinc oxide, nano-cerium oxide and nano-titanium oxide is 1:1:0.5.
[0053] In step c, the oxidation reaction is carried out under multi-stage temperature control conditions, and the reaction temperature is 530-650°C.
[0054] Furthermore, the multi-stage temperature control conditions specifically include:
[0055] Preheating stage: At 540-550℃, inject a mixture of nano-zinc oxide and nano-cerium oxide.
[0056] Low temperature oxidation stage: at 570-600℃, with a temperature of 0.3-0.6m 3 Oxygen is blown in at a flow rate of / min.
[0057] High temperature strengthening stage: at 600-620℃, inject nano-titanium oxide and control the oxygen flow rate to 0.6-0.9m 3 / min.
[0058] Post-processing stage: at 550-570℃, control the oxygen flow rate to 0.3m 3 / min, and with a flow rate of 0.2m 3 / min nitrogen was blown in.
[0059] Among them, the four-stage temperature control optimizes the reaction process step by step. ZnO+CeO2 is used as a catalyst in the preheating and low-temperature oxidation stages to reduce the initial reaction temperature; TiO2 is added in the high-temperature strengthening stage to enhance the oxidation efficiency; and nitrogen is used to stabilize the crystal form in the post-processing stage to reduce energy consumption and reduce by-products.
[0060] Furthermore, the nano auxiliary material is a modified composite auxiliary material, which is obtained by compounding at least two of Al-ZnO, KH-570-CeO and N-TiO.
[0061] Among them, Al-ZnO doped with aluminum enhances catalytic activity, KH-570-CeO2 grafted with silane improves interfacial affinity, and N-TiO2 doped with nitrogen enhances hydrophobicity, further improving the low-temperature dispersibility of the product.
[0062] Further:
[0063] Al-ZnO was prepared by the following steps: dispersing nano zinc oxide in deionized water, adding 0.5% aluminum nitrate by weight, adding 0.1 M sodium hydroxide dropwise to pH 9.0, stirring at 60°C for 2 hours, washing, centrifuging, vacuum drying at 80°C for 12 hours, and calcining in air at 400°C for 3 hours.
[0064] KH-570-CeO was prepared by the following steps: dispersing nano-cerium oxide in ethanol or deionized water, adding 0.5% by weight of KH-570, stirring at 70°C under nitrogen for 3 h, washing, centrifuging, vacuum drying at 60°C for 10 h, and heat treating at 150°C under nitrogen for 2 h.
[0065] N-TiO was prepared by the following steps: dispersing nano-titanium oxide in ethylene glycol, adding 0.3% urea by weight, solvent-thermal reaction at 180°C for 6 hours, washing, centrifugation, vacuum drying at 70°C for 12 hours, and calcining at 350°C under nitrogen atmosphere for 2 hours.
[0066] Furthermore, the multi-stage temperature control conditions specifically include:
[0067] Initial catalytic stage: Al-ZnO was injected at 530 °C and pretreated for 20 min.
[0068] Preheating stage: inject KH-570-CeO at 550℃ and react for 25 minutes.
[0069] Low temperature oxidation stage: at 560-580℃, with a flow rate of 0.25-0.45m 3 Oxygen was introduced at 1000 rpm and the reaction was continued for 35 min.
[0070] High temperature strengthening stage: at 590-610℃, control the oxygen flow rate to 0.55-0.75m 3 / min, reaction time 20min.
[0071] Post-processing stage: at 550-600℃, with a flow rate of 0.18m 3 / min nitrogen is blown in at a flow rate of 0.12m 3 / min, argon gas was blown in at a flow rate of 0.1m 3 A mixture of helium and oxygen was bubbled in at 1 / min for 33 min.
[0072] Furthermore, in the post-processing stage:
[0073] When nitrogen is injected, the temperature is controlled at 580-600℃ and the oxygen flow rate is controlled at 0.25m 3 / min, last for 15min.
[0074] When argon is injected, the temperature is controlled at 570-590°C and the oxygen flow rate is controlled at 0.1m 3 / min, last for 10min.
[0075] When injecting helium, the temperature is controlled at 550-570℃ and the oxygen flow rate is controlled at 0.05m 3 / min, last for 8 minutes.
[0076] Furthermore, the post-treatment includes low-temperature plasma treatment and ultrasonic redispersion.
[0077] Among them, low-temperature plasma treatment (100W, 13.56MHz) enhances the binding force between the auxiliary material and antimony trioxide, and improves the low-temperature dispersibility and hydrophobicity.
[0078] This embodiment also provides an application of low-temperature-adaptable antimony trioxide. The low-temperature-adaptable antimony trioxide prepared by any of the preparation methods described above is used for flame retardant materials, coatings, ceramic sintering and electronic packaging.
[0079] Among them, the antimony trioxide produced through nano-auxiliary materials and multi-stage processes has excellent dispersibility, flame retardancy and hydrophobicity at low temperatures, meeting the diverse needs of flame-retardant plastics, aviation coatings, low-temperature ceramics and electronic packaging; it solves the agglomeration problem of traditional antimony trioxide in extremely cold environments and broadens the application scenarios.
[0080] Furthermore, low-temperature adaptable antimony trioxide is used in flame retardant materials, coatings, ceramic sintering and electronic packaging, specifically including:
[0081] Antimony trioxide is used as a flame retardant for polyvinyl chloride, polypropylene or acrylonitrile-butadiene-styrene copolymer at 0 to -30°C.
[0082] Antimony trioxide is used in aviation or marine equipment coatings at 0 to -30°C.
[0083] Antimony trioxide is used for low temperature sintering of ceramics.
[0084] Antimony trioxide is added to electronic packaging as an antioxidant and moisture-proof additive.
[0085] Specific examples are provided below. The provided examples may enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0086] Example 1
[0087] Take 0.02g of nano-ZnO and 0.02g of nano-CeO2, disperse them in 100mL of deionized water, add 0.01g of PVP, and treat with ultrasound (40kHz, 300W, 25℃) for 45 minutes to form a uniform suspension.
[0088] 100g of refined metallic antimony was placed in the preheating zone of an antimony white furnace, heated to 540°C (heating rate 4°C / min), and kept warm for 10 minutes to completely melt and form antimony liquid.
[0089] The ZnO+CeO2 suspension was injected through a dual-channel ultrasonic atomizer at a rate of 0.08 mL / min for 5 minutes and evenly dispersed on the surface of the antimony liquid.
[0090] The antimony liquid is moved to the low temperature oxidation zone, heated to 570℃, and high purity oxygen (flow rate 0.4m 3 / min, purity 99.5%), and react for 30 minutes to generate initial antimony trioxide vapor.
[0091] Raise the temperature to 600℃ and increase the oxygen flow rate to 0.7m 3 / min, and continue the reaction for 20 minutes.
[0092] Cool down to 550℃, blow in nitrogen (flow rate 0.2m 3 / min)+oxygen (flow rate 0.3m 3 / min), react for 15 minutes, and generate stable steam.
[0093] The antimony trioxide vapor is condensed to 50°C by a liquid nitrogen-assisted cooling device to generate fine powder, which is collected by a cyclone separator and a bag filter.
[0094] The collected powder was placed in a low-temperature plasma device (100 W, 13.56 MHz, argon flow 0.1 L / min) and treated for 5 minutes.
[0095] The powder was dispersed in deionized water (50 mL) containing 0.01% PVP and ultrasonicated (20 kHz, 200 W) for 10 minutes.
[0096] The exhaust gas is treated by activated carbon adsorber and catalytic combustion device (300℃, CuO / Al2O3 catalyst), and the emission reaches the standard (particulate matter ≤5mg / m 3 , VOCs≤30ppm).
[0097] The waste liquid is recycled after acid-base neutralization (pH 7.0).
[0098] The antimony trioxide powder was collected, dried (80°C, 6 hours), and sealed for storage.
[0099] Example 2
[0100] Disperse 0.02g of nano-ZnO and 0.02g of nano-CeO2 in 100mL of deionized water, add 0.01g of PVP, and ultrasonicate (40kHz, 300W, 25°C) for 45 minutes to form a uniform suspension. Disperse 0.01g of nano-TiO2 in 50mL of deionized water, add 0.005g of KH-550, and ultrasonicate (40kHz, 300W, 25°C) for 30 minutes to form a uniform suspension.
[0101] 100g of refined metallic antimony was placed in the preheating zone of an antimony white furnace, heated to 540°C (heating rate 4°C / min), and kept warm for 10 minutes to completely melt and form antimony liquid.
[0102] The ZnO+CeO2 suspension was injected through a dual-channel ultrasonic atomizer at a rate of 0.08 mL / min for 5 minutes and evenly dispersed on the surface of the antimony liquid.
[0103] The antimony liquid is moved to the low temperature oxidation zone, heated to 570℃, and high purity oxygen (flow rate 0.4m 3 / min, purity 99.5%), and react for 30 minutes to generate initial antimony trioxide vapor.
[0104] Raise the temperature to 600℃ and increase the oxygen flow rate to 0.7m 3 / min, and continue the reaction for 20 minutes.
[0105] Cool down to 550℃, blow in nitrogen (flow rate 0.2m 3 / min)+oxygen (flow rate 0.3m 3 / min), react for 15 minutes, and generate stable steam.
[0106] The antimony trioxide vapor is condensed to 50°C by a liquid nitrogen-assisted cooling device to generate fine powder, which is collected by a cyclone separator and a bag filter.
[0107] The collected powder was placed in a low-temperature plasma device (100 W, 13.56 MHz, argon flow 0.1 L / min) and treated for 5 minutes.
[0108] The powder was dispersed in deionized water (50 mL) containing 0.01% PVP and ultrasonicated (20 kHz, 200 W) for 10 minutes.
[0109] The exhaust gas is treated by activated carbon adsorber and catalytic combustion device (300℃, CuO / Al2O3 catalyst), and the emission reaches the standard (particulate matter ≤5mg / m 3 , VOCs≤30ppm).
[0110] The waste liquid is recycled after acid-base neutralization (pH 7.0).
[0111] The antimony trioxide powder was collected, dried (80°C, 6 hours), and sealed for storage.
[0112] Example 3
[0113] Disperse 10g of nano-ZnO (particle size 15-20nm) in 100mL of deionized water, add 0.05g of aluminum nitrate, and stir until dissolved. Slowly add 0.1M sodium hydroxide (0.5mL / min) to pH 9.0, and stir at 60°C for 2 hours (500rpm). Wash with deionized water and ethanol three times each, centrifuge at 8000rpm for 10 minutes, and vacuum dry at 80°C for 12 hours. Calcinate at 400°C in air for 3 hours (heating rate 2°C / min) to obtain Al-ZnO.
[0114] Disperse 10g of nano-CeO2 (particle size 10-15nm) in 100mL of ethanol / deionized water (1:1) and add 0.05g of silane coupling agent KH-570 (98% purity). Stir at 70°C under nitrogen for 3 hours (600rpm). Wash three times with ethanol, centrifuge at 9000rpm for 8 minutes, and vacuum dry at 60°C for 10 hours. Heat treat at 150°C under nitrogen for 2 hours to obtain KH-570-CeO2.
[0115] Take 10g of nano-TiO2 (particle size 10-12nm) and disperse it in 80mL of ethylene glycol. Add 0.03g of urea (purity 99%). Transfer it to a 100mL polytetrafluoroethylene-lined autoclave and perform solvent thermal reaction at 180℃ for 6 hours (heating rate 3℃).
[0116] The sample was washed with deionized water and ethanol three times each, centrifuged at 10,000 rpm for 5 minutes, and dried under vacuum at 70°C for 12 hours.
[0117] Calcinate at 350℃ in nitrogen for 2 hours (heating rate 1.5℃ / min) to obtain N-TiO2.
[0118] Disperse 0.02g of Al-ZnO in 100mL of deionized water, add 0.01g of PVP, and treat with ultrasonic waves (40kHz, 400W, 25°C) for 60 minutes to obtain the first auxiliary material solution. Disperse 0.02g of KH-570-CeO2 in 100mL of ethanol, add 0.005g of PEG-2000, and treat with ultrasonic waves (40kHz, 400W) for 45 minutes to obtain the second auxiliary material solution. Disperse 0.01g of N-TiO2 in 50mL of deionized water, add 0.005g of KH-550, and treat with ultrasonic waves (40kHz, 400W) for 30 minutes to obtain the third auxiliary material solution.
[0119] 100 g of refined metallic antimony was placed in the initial catalytic zone of an antimony white furnace, heated to 530° C. (heating rate 3° C. / min), and kept warm for 10 minutes.
[0120] The first auxiliary material solution was injected through a three-channel ultrasonic nebulizer at a rate of 0.06 mL / min for 5 minutes, and the pretreatment lasted for 20 minutes.
[0121] The antimony solution was moved to the preheating zone, heated to 550°C, and the second auxiliary material solution was injected, continued for 5 minutes, and reacted for 25 minutes.
[0122] The antimony liquid is moved to the low temperature oxidation zone, heated to 560℃, and high purity oxygen (flow rate 0.35m 3 / min, purity 99.5%), and react for 35 minutes to generate antimony trioxide vapor.
[0123] The temperature was raised to 590°C and the oxygen flow rate was increased to 0.65m 3 / min, inject the third auxiliary material liquid, continue for 5 minutes, and react for 20 minutes.
[0124] 580℃, nitrogen gas (0.18m 3 / min)+oxygen(0.25m 3 / min), 15 minutes. 570℃, bubbling argon (0.12m 3 / min)+oxygen(0.1m 3 / min), 10 minutes. 550℃, helium (0.1m 3 / min)+oxygen(0.05m 3 / min), 8 minutes.
[0125] The antimony trioxide vapor is condensed to 50°C by a liquid nitrogen-assisted cooling device to generate fine powder, which is collected by a cyclone separator and a multi-stage bag filter.
[0126] The powder was placed in a low-temperature plasma device (120 W, 13.56 MHz, argon flow 0.1 L / min) and treated for 6 minutes.
[0127] The powder was dispersed in deionized water (50 mL) containing 0.005% PVP + 0.002% KH-550 and treated with ultrasound (20 kHz, 250 W) for 12 minutes.
[0128] 200℃, 10 -1 Pa, vacuum heat treatment for 10 minutes.
[0129] The exhaust gas is purified by activated carbon adsorption + catalytic combustion (280℃, Pd / Al2O3) + low-temperature plasma, and the emission reaches the standard (particulate matter ≤3mg / m 3 , VOCs≤20ppm).
[0130] The waste liquid is recycled after acid-base neutralization (pH 7.0) + nanofiltration treatment.
[0131] The antimony trioxide powder was collected, dried (80°C, 6 hours), and sealed for storage.
[0132] Comparative Example
[0133] 100g of refined metallic antimony was placed in a single-stage temperature control zone of an antimony white furnace, heated to 650°C (heating rate 5°C / min), and kept warm for 15 minutes to completely melt and form antimony liquid.
[0134] Heat up to 700℃, blow in air (flow rate 0.8m 3 / min), and react for 60 minutes to generate antimony trioxide vapor.
[0135] The antimony trioxide vapor is condensed to 50°C by a liquid nitrogen-assisted cooling device to generate fine powder, which is collected by a cyclone separator and a bag filter.
[0136] The antimony trioxide powder was collected, dried (80°C, 6 hours), and sealed for storage.
[0137] The exhaust gas is treated by activated carbon adsorber and catalytic combustion device (300℃, CuO / Al2O3 catalyst), and the emission reaches the standard (particulate matter ≤10mg / m 3 , VOCs ≤ 50ppm). No waste liquid is generated.
[0138] The antimony trioxide prepared in Examples 1 to 3 and the comparative example was subjected to the following tests:
[0139] Take 0.2 g of powder, dissolve it in nitric acid (1:1), dilute to 10 mL, and test the purity.
[0140] Take 0.1 g of powder, disperse it in deionized water, treat it with ultrasound for 5 minutes, and measure D10, D50, and D90.
[0141] 1 g of antimony trioxide powder was mixed with 10 g of PVC powder, placed in a -30°C thermostat for 24 hours, and the low-temperature dispersibility was measured (centrifugation method, 3000 rpm, 10 minutes).
[0142] 1 g of antimony trioxide and 10 g of PVC were made into standard specimens (120×6.5×3 mm), and the LOI value was tested at -30°C.
[0143] Take 0.5 g of powder and press it into a tablet. Measure the contact angle by the water drop method and repeat 3 times to obtain the average value.
[0144] The test data is shown in the following table:
[0145]
[0146] As can be seen from the table, the low-temperature dispersibility of Examples 1 to 3 (increased by 46.7% to 60.0%) far exceeds that of the comparative example, with Example 3 achieving the best results, effectively solving the low-temperature agglomeration problem. The low-temperature flame retardancy of Examples 1 to 3 (30.2 to 30.8) is higher than that of the comparative example (27.5), with Example 3 being the best (30.8), making it suitable for use as an extremely cold flame-retardant material. The hydrophobicity (contact angle, 122 to 135°) of Examples 1 to 3 far exceeds that of the comparative example (85°), with Example 3 being the best, meeting the requirements of aviation / marine coatings.
[0147] The principles and implementation methods of the present invention are described herein using specific examples. The description of the above embodiments is only intended to help understand the method and core ideas of the present invention. The above are only preferred implementation methods of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, and all of these should fall within the scope of protection of the present invention.
Claims
1. A method for preparing low-temperature adaptable antimony trioxide, characterized in that: The steps include: a) heating and melting the metal ladder to form antimony liquid; b) adding a nano material to the antimony solution, wherein the nano material comprises at least one of nano zinc oxide, nano cerium oxide and nano titanium oxide; c) blowing in an oxygen-containing atmosphere to carry out an oxidation reaction to generate antimony trioxide vapor; d) cooling the antimony trioxide vapor to 15-80° C. to generate antimony trioxide powder; e) collecting the powder and performing post-processing to obtain the low-temperature adaptable antimony trioxide.
2. The preparation method according to claim 1, wherein: In step a), the heating temperature is 530-650° C.; In step b), the total mass of the nano-auxiliary materials is 0.03% to 0.05% of the mass of the antimony liquid, wherein the mass ratio of nano-zinc oxide, nano-cerium oxide and nano-titanium oxide is 1:1:0.5; In step c), the oxidation reaction is carried out under multi-stage temperature control conditions, and the reaction temperature is 530-650°C.
3. The preparation method according to claim 2, characterized in that The multi-stage temperature control conditions specifically include: Preheating stage: inject nano zinc oxide and nano cerium oxide mixed solution at 540-550℃; Low temperature oxidation stage: at 570-600℃, with a temperature of 0.3-0.6m 3 / min flow rate to blow in oxygen; High temperature strengthening stage: at 600-620℃, inject nano-titanium oxide and control the oxygen flow rate to 0.6-0.9m 3 / min; Post-processing stage: at 550-570℃, control the oxygen flow rate to 0.3m 3 / min, and with a flow rate of 0.2m 3 / min nitrogen was blown in.
4. The preparation method according to claim 2, characterized in that The nano auxiliary material is a modified composite auxiliary material, which is obtained by compounding at least two of Al-ZnO, KH-570-CeO and N-TiO.
5. The preparation method according to claim 4, characterized in that: The Al-ZnO is prepared by the following steps: dispersing nano zinc oxide in deionized water, adding 0.5% aluminum nitrate by weight of the nano zinc oxide, adding 0.1M sodium hydroxide dropwise to a pH of 9.0, stirring at 60°C for 2 hours, washing, centrifuging, vacuum drying at 80°C for 12 hours, and calcining in air at 400°C for 3 hours; The KH-570-CeO is prepared by the following steps: dispersing nano-cerium oxide in ethanol or deionized water, adding 0.5% by weight of KH-570, stirring at 70°C under nitrogen protection for 3 hours, washing, centrifuging, vacuum drying at 60°C for 10 hours, and heat treating at 150°C under nitrogen atmosphere for 2 hours; The N-TiO is prepared by the following steps: dispersing nano-titanium oxide in ethylene glycol, adding 0.3% urea by weight, solvent thermal reaction at 180°C for 6 hours, washing, centrifuging, vacuum drying at 70°C for 12 hours, and calcining at 350°C under a nitrogen atmosphere for 2 hours.
6. The preparation method according to claim 4 or 5, characterized in that The multi-stage temperature control conditions specifically include: Initial catalytic stage: Al-ZnO injection at 530°C, pretreatment for 20 min; Preheating stage: inject KH-570-CeO at 550℃ and react for 25min; Low temperature oxidation stage: at 560-580℃, with a flow rate of 0.25-0.45m 3 / min oxygen was introduced and the reaction was continued for 35min; High temperature strengthening stage: at 590-610℃, control the oxygen flow rate to 0.55-0.75m 3 / min, reaction time 20min; Post-processing stage: at 550-600℃, with a flow rate of 0.18m 3 / min nitrogen is blown in at a flow rate of 0.12m 3 / min, argon gas was blown in at a flow rate of 0.1m 3 A mixture of helium and oxygen was bubbled in at 1 / min for 33 min.
7. The preparation method according to claim 6, characterized in that In the post-processing stage: When nitrogen is injected, the temperature is controlled at 580-600℃ and the oxygen flow rate is controlled at 0.25m 3 / min, lasting 15min; When argon is injected, the temperature is controlled at 570-590°C and the oxygen flow rate is controlled at 0.1m 3 / min, lasting 10min; When injecting helium, the temperature is controlled at 550-570℃ and the oxygen flow rate is controlled at 0.05m 3 / min, last for 8 minutes.
8. The preparation method according to claim 3, characterized in that The post-treatment includes low-temperature plasma treatment and ultrasonic redispersion.
9. An application of low-temperature adaptable antimony trioxide, characterized in that: The low-temperature adaptable antimony trioxide prepared by the preparation method according to any one of claims 1 to 8 is used for flame retardant materials, coatings, ceramic sintering and electronic packaging.
10. The use according to claim 9, characterized in that The low-temperature adaptable antimony trioxide is used in flame retardant materials, coatings, ceramic sintering and electronic packaging, specifically including: The antimony trioxide is used as a flame retardant for polyvinyl chloride, polypropylene or acrylonitrile-butadiene-styrene copolymer at 0 to -30°C. The antimony trioxide is used for aviation or marine equipment coatings at 0 to -30°C. The antimony trioxide is used for low temperature sintering of ceramics; The antimony trioxide is added to electronic packaging as an antioxidant and moisture-proof additive.